A Rare Presentation of Pseudomembranous Colitis in a COVID-19 patient. (28th October 2020) - Jabbar, A; Rana, T; Ilyas, G; Baqir, A; Emechebe, D; Agaronov, M
Abstract: Introduction/Objective: Recent reports suggest that though COVID-19 is predominantly a respiratory pathogen, one of its presenting features can be gastrointestinal symptoms. We hereby present a case of a female with COVID-19 infection whose hospital course was complicated by colonic pseudo-obstruction caused by pseudomembranous colitis resulting in an emergent hemicolectomy. Methods: A 59-Year-old female with history of hypertension, diabetes, and breast cancer post mastectomy presented with pneumonia and was confirmed to be COVID-19 positive. She was admitted to the hospital and was treated with Azithromycin for 6 days. Patient developed constipation on day six of hospitalization and started having abdominal pain on day eight with elevated WBC count. Imaging showed distension of cecum and proximal colon. She underwent exploratory laparotomy which revealed a necrotic appearing cecum that was massively dilated and had a serosal tear. These findings prompted emergent hemicolectomy with loop ileostomy. Grossly cecum was black/green, dilated, thin walled with a 5 x 5 cm yellow green raised plaques. Microscopy of the plaques revealed focal erosion of colonic mucosa with overlying acute inflammatory cells, fibrin deposits, mucus, and necrotic epithelial cells consistent with pseudomembranous colitis. Conclusion: Review of literature shows no reported cases of intestinal pseudo-obstruction due to pseudomembranous colitis in a COVID-19 patient. Not only this, but there are also only a limited number of case studies of pseudomembranous colitis presenting as intestinal pseudo-obstruction without diarrhea. Though this patient's presentation could be from Clostridium difficile infection secondary to Azithromycin, it is not a common antibiotic to cause this. Also, one of the known causes of pseudomembranous colitis is ischemia. Given that COVID-19 infection is a pro-thrombotic condition, possible ischemia secondary to COVID-19 infection related coagulopathy should also be a consideration.